Woman as the Goddess, the Mother, and the Lover: A Literary Analysis of Selected Poems of J. P. Clark - Yakubu, Anthonia M. (NIU Journal of Humanities, 2024)
Women have traditionally been viewed from the images of the supernatural, motherhood, and the sensual, and depending on the beholder and the context, these images come with layers of negativity and/or positivity ascribed to them. Many communities categorise women into these separate and distinct entities, and in few occasions, women embody these social types. Under each of these entities are sub-types and kinds that women are believed to portray; for example, under the sensual, women are also believed to be sorcerers, wicked, calculating, murderers, among other negativities. Under motherhood, women are generally perceived as caregivers, not ambitious, long suffering, sacrificial, homely, etc. As supernatural beings, women are generally feared, adored, entreated, powerful, and vengeful. Women have over the centuries contended with these prescribed roles and traits and have also come to believe many of these about themselves. John Pepper Clark-Bekederemo, popularly known as J.P. Clark, a first-generation Nigerian poet and dramatist analysed a number of these perceptions and beliefs about women in his poetry, using the Niger Delta terrain as the backdrop. His robust education notwithstanding, a number of his poems dwell on the strengths, weaknesses, presence, and invisibility of women, particularly those who were people he related with. From the early 60s, when he published his first poetry collection, to the 21 st century, nothing really has changed much in the general views about women. Instead, in spite of the gallant strides women have made personally and for the common good, they are still regarded as subservient and incomplete. Keywords: Poetry, Women, JP Clark, Patriarchy, Archetypal, Images